2013
DOI: 10.1055/s-0033-1355894
|View full text |Cite
|
Sign up to set email alerts
|

Liver Remnant Regeneration in Donors After Living Donor Liver Transplantation: Long-Term Follow-Up Using CT and MR Imaging

Abstract: Purpose: To assess liver remnant volume regeneration and maintenance, and complications in the long-time follow-up of donors after living donor liver transplantation using CT and MRI. Materials and Methods: 47 donors with a mean age of 33.5 years who donated liver tissue for transplantation and who were available for follow-up imaging were included in this retrospective study. Contrast-enhanced CT and MR studies were acquired for routine follow-up.?Two observers evaluated pre- and postoperative images regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 10 publications
1
16
0
2
Order By: Relevance
“…One report included serial assessments postdonation, and findings show that volume regeneration continues beyond the first year postdonation (25); this report showed that ultimately the regenerated liver volumes in the vast majority of assessments were indistinguishable from preoperative volumes. The two additional long-term cross-sectional follow-up studies also found little to no pre- versus postdonation mean differences in total volumes (10,26).…”
Section: Long-term Outcomesmentioning
confidence: 81%
See 2 more Smart Citations
“…One report included serial assessments postdonation, and findings show that volume regeneration continues beyond the first year postdonation (25); this report showed that ultimately the regenerated liver volumes in the vast majority of assessments were indistinguishable from preoperative volumes. The two additional long-term cross-sectional follow-up studies also found little to no pre- versus postdonation mean differences in total volumes (10,26).…”
Section: Long-term Outcomesmentioning
confidence: 81%
“…The two additional long-term cross-sectional follow-up studies also found little to no pre- versus postdonation mean differences in total volumes (10,26). No differences were noted in late-term total volume as a function of type of graft donated (10,25). However, samples in the studies were relatively small (Table 2), limiting any ability to identify graft-related differences.…”
Section: Long-term Outcomesmentioning
confidence: 86%
See 1 more Smart Citation
“…In a study by Klink et al, after donation of a right liver lobe, the remaining left lobe had a mean volume of 36.1% of the TLV (baseline) (89). After 1 month, FRL was 54.8% of the pre-transplantation TLV (53.6% DoH).…”
Section: Future Remnant Livermentioning
confidence: 99%
“…After 1 month, FRL was 54.8% of the pre-transplantation TLV (53.6% DoH). After 3 months, 80% of the pre-transplantation TLV was restored (146% DoH) and after 12 months the post-transplantation volume was equal to or even more than 100% of the initial TLV (267% DoH) (89). This shows the value of a longer interval between the induction of hypertrophy and surgery.…”
Section: Future Remnant Livermentioning
confidence: 99%